2002
DOI: 10.1128/jcm.40.11.4037-4044.2002
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acquired Toxoplasmosis in Immunocompetent Adult Patients in French Guiana

Abstract: The most common presentation of symptomatic postnatally acquired toxoplasmosis in immunocompetent patients is painless cervical adenopathy. Acute visceral manifestations are associated in rare cases. We report 16 cases of severe primary toxoplasmosis diagnosed in French Guiana during a 6.5-year period. All of the subjects were immunocompetent adults hospitalized with clinical presentations consisting of a marked, nonspecific infectious syndrome accompanied by an altered general status with at least one viscera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
167
0
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(186 citation statements)
references
References 34 publications
3
167
0
12
Order By: Relevance
“…This may also explain the high frequency (20 % of 97 cases) of ocular involvement in the Victoria outbreak, in British Columbia where an atypical cougar isolate was suspected (Burnett et al, 1998), and the 100-fold higher incidence of ocular toxoplasmosis in patients born in Africa compared to patients born in Britain (Gilbert et al, 1999). The virulence of atypical strains is also obvious in the cases of severe toxoplasmosis observed in immunocompetent patients with multi-organ failure (Carme et al, 2002). Several deaths due to toxoplasmosis were observed in these immunocompetent patients.…”
Section: Genotypes and Expression Of Toxoplasma Virulence In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…This may also explain the high frequency (20 % of 97 cases) of ocular involvement in the Victoria outbreak, in British Columbia where an atypical cougar isolate was suspected (Burnett et al, 1998), and the 100-fold higher incidence of ocular toxoplasmosis in patients born in Africa compared to patients born in Britain (Gilbert et al, 1999). The virulence of atypical strains is also obvious in the cases of severe toxoplasmosis observed in immunocompetent patients with multi-organ failure (Carme et al, 2002). Several deaths due to toxoplasmosis were observed in these immunocompetent patients.…”
Section: Genotypes and Expression Of Toxoplasma Virulence In Humansmentioning
confidence: 99%
“…Among these three lineages, the type II is largely predominant in published studies. In France, it is found in more than 90 % of human congenital toxoplasmosis, but also in all isolates originating from a large variety of animals (Ajzenberg et al, 2002). More studies are needed to confirm if this pattern of Toxoplasma population is observed throughout Europe.…”
Section: Toxoplasma Genotypes the Three Main Clonal Lineagesmentioning
confidence: 99%
“…These isolates showed distinct and atypical genotypes, and neither has been described previously. Although T. gondii infection is asymptomatic in most immunocompetent hosts, severe cases of toxoplasmosis caused by atypical genotypes have been described in the Amazon region of French Guiana (19) (20) (21) .…”
Section: Statistical Analysesmentioning
confidence: 99%
“…10 Recently, generalized toxoplasmosis in immunocompetent adult human beings caused by strains of T. gondii exhibiting atypical genotypes that were highly virulent in mice has been described. 3,4 Similar atypical genotypes have been isolated from both domestic and wild mammals. 12,13 A 10-year-old male, neutered domestic shorthair cat was referred to the Small Animal Clinic at the University of Bern (Bern, Switzerland) with a 1-week history of anorexia, vomiting, diarrhea, and fever; the symptoms had been unresponsive to treatment with antibiotics (amoxicillinclavulanic acid), nonsteroidal anti-inflammatory drugs (tolfenamic acid), and antiemetics (metoclopramide).…”
mentioning
confidence: 99%